2004
DOI: 10.2134/agronj2004.0832
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Flooding and Water Table Effects on Two Sugarcane Genotypes

Abstract: et al., 1998). Some EAA fields had as much as 300 cm of soil above the limestone bedrock when they were Sugarcane (Saccharum spp.) in Florida is increasingly exposed to first drained and used for agriculture. Depth of soil to periodic floods and high water tables for extended durations. We bedrock varies, but a small number of sugarcane fields evaluated the effects of periodic flooding, followed by drainage, on morphological characteristics and cane and sugar yields of two sugar-now have less than 40 cm of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 13 publications
5
43
0
2
Order By: Relevance
“…Therefore, in sweet sorghum, sucrose synthesis and the ability to transport sucrose to sink may not be affected by flooding conditions. A similar response has also been reported in sugarcane (Hasan et al, 2003;Glaz et al, 2004;Glaz & Gilbert, 2006) and sweet sorghum under drought stress (Massacci et al, 1996) indicating that sucrose synthesis and transportation are not affected by stress. The consistent higher juice quality of Wray may also be explained by its ability to form significantly higher aerenchyma in plants' axes or lateral roots as well as ability to develop roots in water.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, in sweet sorghum, sucrose synthesis and the ability to transport sucrose to sink may not be affected by flooding conditions. A similar response has also been reported in sugarcane (Hasan et al, 2003;Glaz et al, 2004;Glaz & Gilbert, 2006) and sweet sorghum under drought stress (Massacci et al, 1996) indicating that sucrose synthesis and transportation are not affected by stress. The consistent higher juice quality of Wray may also be explained by its ability to form significantly higher aerenchyma in plants' axes or lateral roots as well as ability to develop roots in water.…”
Section: Discussionsupporting
confidence: 84%
“…The internal portion of axes, soil-covered stem and 3rd node of the stalk above water level of each plant were visually scored for relative size of pithy area with aerenchyma formation according to Glaz et al (2004). Briefly, the ratings of pithy area with A flood-free period of sweet sorghum 347 aerenchyma formation ranged from 0 for none to 5 for an area that was equal to about 70% of the stalk diameter.…”
Section: Observation Of Root Anatomy and Aerenchyma Formation In Axesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flooding also decreased stem weight on 90 DAT, which is consistent with a previous finding that water logging over 15-60 d at the grand growth phase decreased yield by approximately 5-30% because of the lack of nutrition and water uptake (Gomathi et al, 2014), while 3 mo of flooding decreased the yield by 18-37% in plant cane and 61-63% in a second ratoon (Gilbert et al, 2008). However, growth and yield loss may depend on the tolerance of the cultivar, as it has been shown that there is loss in yield in CP 95-1376 but not in CP 95-1429 (Glaz et al, 2004b), whereas high water table had no effect on yields of CP 72-2086 and CP 82-1172 but adversely affected CP 80-1743, resulting in a decrease in yield by 25.1% (Glaz et al, 2002). Thus, plants may require more time to recover their root system and growth.…”
Section: Sugar Content and Sugar Yieldmentioning
confidence: 99%
“…Glaz et al (2004a) studied the effect of 7-day episodes of flooding with target drained flood water tables from 16-50 cm BSS for 2 weeks with each treatment repeating five to nine cycles in each crop year for up to second ratoon. Results indicated that two cultivars tested had no yield loss with periodic flooding or changing level of the water table.…”
Section: Waterlogging and Flooding Tolerancementioning
confidence: 99%